An inherited variant in the gene coding for vitamin D‐binding protein and survival from cutaneous melanoma: a BioGenoMEL study. (11th December 2013) - Davies, John R.; Field, Sinead; Randerson‐Moor, Juliette; Harland, Mark; Kumar, Rajiv; Anic, Gabriella M.; Nagore, Eduardo; Hansson, Johan; Höiom, Veronica; Jönsson, Göran; Gruis, Nelleke A.; Park, Jong Y.; et al.
Summary An association between low serum vitamin D levels and poorer melanoma survival has been reported. We have studied inheritance of a polymorphism of the GC gene, rs2282679, coding for the vitamin D‐binding protein, which is associated with lower serum levels of vitamin D, in a meta‐analysis of 3137 melanoma patients. The aim was to investigate evidence for a causal relationship between vitamin D and outcome (Mendelian randomization). The variant was not associated with reduced overall survival (OS) in the UK cohort, per‐allele hazard ratio (HR) for death 1.23 (95% confidence interval (CI) 0.93, 1.64). In the smaller cohorts, HR in OS analysis was 1.07 (95% CI 0.88, 1.3) and for all cohorts combined, HR for OS was 1.09 (95% CI 0.93, 1.29). There was evidence of increased melanoma‐specific deaths in the seven cohorts for which these data were available. The lack of unequivocal findings despite the large sample size illustrates the difficulties of implementing Mendelian randomization.